Data Envelopment Analysis on Energy Efficiencies of Transport Modes in Iskandar Malaysia Region (MATEMATIKA, 2011)
The goal of this paper is to assess and evaluate the annual productivity of transport modes in Iskandar Malaysia with the aim of discovering the inefficient year. Transport mode is one of the energy-consuming sectors. The paper used Data Envelopment Analysis (DEA) technique to achieve this purpose. It also employed multiple linear regression approach to estimate future energy performance. Spearman's correlation coefficient revealed that the relationship between the variables selected is isotonic, and it shows there is a perfectly positive relationship between the variables selected. Hence, DEA results revealed that in the year 2005, efficiency, achievement was achieved under variable return to scale, but was not in 2005 under constant return to scale assumptions. The excess energy and shortfalls in productivity were highlighted. Besides that DEA set targets for improving productivity. Keywords: Energy efficiency; carbon dioxide emissions; transportation sector 2010 Mathematics Subject Classification 90B06; 91B76